Penggunaan Internet Sebagai Media Baru dalam Pembelajaran - Abdoel Gafar (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
The developement of information and communication technology ( ICT) has changed our way of looking at things including teaching media. This article discusses the advantages and disadvantages of using internet in teaching and learning process. Key word: Internet,  media pembelajaran